Respuesta :
Answer:
y = three-halves x minus 3
Step-by-step explanation:
Subtract 3x from both sides of the original equation.
-2y = -3x +6
Divide by -2
y = 3/2x -3
Answer:
The slope intercept form of 3x - 2y = 6 is [tex]y = \frac{3x}{2} - 3[/tex]
In other words, y = three-halves x minus 3
Step-by-step explanation:
Given:
3x - 2y = 6
Required:
Proper representation of the slope intercept form
To get the proper system that represents the given expression, we have to make y the subject of the formula.
Follow the steps below
Step 1: Write out the expression
3x - 2y = 6
Step 2: Take 3x to the other side of the equation
- 2y = 6 - 3x
Step 3: Multiply both sides by -1
-1 * -2y = -1 * (6 - 3x)
Step 4: Write out result
2y = 3x - 6
Step 5: Divide both sides by 2
[tex]\frac{2y}{2} = \frac{3x - 6}{2}[/tex]
[tex]y = \frac{3x - 6}{2}[/tex]
Step 6: Split fraction
[tex]y = \frac{3x}{2} - \frac{6}{2}[/tex]
[tex]y = \frac{3x}{2} - 3[/tex]
Hence, the slope intercept form of 3x - 2y = 6 is [tex]y = \frac{3x}{2} - 3[/tex]
In other words, y = three-halves x minus 3